Reef fish diversity in the Legon Bajak Port, Kemujan Island, Karimunjawa National Park - Siti Lathifah Maulany; Ardyan Pramudya Kurniawan (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Karimunjawa National Park provides substantial reef fish resources, leading to higher market demand for reef fish production. This study aims to determine the diversity of reef fish, particularly in regions where fishing boats dock, specifically in Legon Bajak Port, Kemujan Island, Karimunjawa National Park, Jepara, Central Java. The findings of this investigation should enrich previous studies. The study was conducted on the right and left sides of the Legon Bajak Port. The visual count of belt transects was used to obtain data on reef fish. The study results obtained the number of reef fish at the Legon Bajak Port was 2769 individuals/500 m2 on the right and 1809 individuals/500 m2 on the left side, representing 40 species, 26 genera, and 13 families. Istigobius rigilius had the largest density of individuals, with 233 individuals/500 m2. The fish diversity index (H') value on the right side of the Legon Bajak Port was 3.24, which includes the high category, and on the left side was 2.89, which includes the medium category. The dominance index (D) was between 0.05 and 0.06 (low), while the uniformity index (E) was between 0.74 and 0.83 (unstable in a stable community).